The Design of UrMus as a Meta-Environment for Mobile Music - George Essl; Sang Won Lee (Journal of Creative Music Systems, 2017)
UrMus is a meta-environment to support mobile music. By aiming to facilitate a design philosophy of openness and flexibility, it provides wide ranging technical support to be leveraged for diverse forms of musical expression on mobile devices. UrMus has evolved over a period of six years to support wide ranging music performance practices such as collaborative mobile live coding, networked mobile performances, and the use of machine-learning in mobile music. By taking a multi-paradigmatic approach, UrMus allows the user investigate representations for mobile music program directly on the mobile device.